Symmetric Dimethylarginine Predicts Previously Undetected Atrial Fibrillation in Patients With Ischemic Stroke - Juliane Hannemann; Katrin Wasser; Yoana Mileva; Fiona Kleinsang; Mario Schubert; Edzard Schwedhelm; Kaomei Guan; Rolf Wachter; Rainer Böger (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Atrial fibrillation (AF) is a stroke risk factor that often remains undetected at hospital admission. Long‐term Holter monitoring helps to identify patients with previously unrecognized AF. Asymmetric (ADMA) and symmetric dimethylarginine (SDMA) are elevated in AF in cross‐sectional studies. We analyzed ADMA, SDMA, and other L‐arginine metabolites to assess their association with AF in the Find‐AF trial. Methods and Results We included 280 patients presenting with acute cerebral ischemia. Patients presenting in sinus rhythm received 7‐day Holter‐ECG. Biomarkers were quantified by ultra‐performance liquid chromatography–tandem mass spectrometry. We also analyzed protein methylation and L‐arginine‐related metabolites in human induced pluripotent stem cell‐derived cardiomyocytes in vitro. ADMA and SDMA were elevated in 44 patients who presented with AF. SDMA, but not ADMA, was significantly elevated in patients newly diagnosed with AF in Holter‐ECG as compared with those in sinus rhythm. SDMA plasma concentration >0.571 μmol/L significantly predicted presence of AF in Holter‐ECG (area under the curve=0.676 [0.530–0.822]; P=0.029; sensitivity 0.786, specificity 0.572). SDMA levels further increased in patients with AF during the first 24 hours in hospital, and ADMA levels remained stable. In vitro, induced pluripotent stem cell‐derived cardiomyocytes showed increased symmetric protein methylation and elevated SDMA during rapid pacing (2.0 Hz versus 0.5 Hz), whereas asymmetric protein methylation and ADMA were unchanged. Conclusions SDMA at admission was significantly elevated in stroke patients presenting with AF and showed a moderate but significant prospective association with previously unrecognized AF. Thus, stroke patients with elevated SDMA concentration at admission may specifically benefit from extended Holter‐ECG monitoring.